Evaluation of Mechanical properties for polypropylene Modified Asphalt concrete Mixtures (International Journal of Scientific Research and Management (IJSRM), 2017)
It is noticeable that the increase of road traffic during the last two decades in addition to the insufficient degree of maintenance caused an accelerated deterioration of road structure. These roads show early signs of distress such as rutting, cracking, low temperature cracking, ageing and stripping. Heavier loads and higher traffic volume demand higher performance of pavement. Excellent performance of pavement requires bitumen that is less susceptible to high temperature, rutting or low temperature cracking. Several additives are used to increase the performance of bitumen and the quality of the produced mixtures. Polymers are considered the most widely used additives in asphalt modification that give better performance. The performance of the Polymer-modified asphalt depends on the type and the level of modification the used polymer. The choice of modification level and t modification type depends on the physical properties of the polymer, and its compatibility with bitumen. The polymer can be loosely classified into two categories, Plastomers and Elastomers. The results indicated that, the addition of polypropylene generally improved the mechanical properties of the mixture regardless of the percentage of polymers that added and (PP) content of 5%. it can be noticed that the performance of PP-modified asphalt mixtures is better compared with unmodified asphalt concrete mixtures modifier because it has the highest Marshall Stiffness, indirect tensile strength and unconfined compressive strength